The Identification of Higher Order Thinking Skill Domain in The Eleventh Grade English Lesson Plan at SMK N 1 Singaraja - Surya, Cok Istri Rahma Pratami; Wedhanti, Nyoman Karina; Juniarta, Putu Adi Krisna (The Art of Teaching English as a Foreign Language (TATEFL), 2021)
This research aimed to identify the cognitive domains of Higher Order Thinking Skills that appear in the four English Lesson Plans in eleventh grade and the most dominant cognitive domain of Higher Order Thinking Skill used in the four English lesson plans in eleventh grade. This research used descriptive qualitative research design. The setting of this research is in SMK N 1 Singaraja. The subject of this research were the English lesson plans and one of the teachers in SMK N 1 Singaraja. The data were collected by using documentation, checklist, and interview guide. The results of this research are, (1) There are two cognitive domains (C4 & C6) appear in those four lesson plans, (2) The most cognitive domain appear in the four English lesson plans is C6 with the operational verb is arrange.